EmoPlay: Inovasi Media Pembelajaran Interaktif Berbasis Model ADDIE sebagai Sarana Pengenalan dan Regulasi Emosi Anak Usia Dini - Siti Fadillah; Fatiha Fatiha (UIN Siber Syekh Nurjati Cirebon, 2025)
Social-emotional development is an important aspect that affects the ability of early childhood to interact, learn, and adapt to their environment. Observation results at RA Al-Ikhlas Kedawung show that some children still have difficulty in recognizing and managing their emotions, such as being easily angry, crying, or having difficulty waiting for their turn. This condition indicates the need for learning media that can stimulate children's ability to regulate emotions in an interesting and interactive way. This research aims to develop a digital-based learning media called EmoPlay, which is designed to help early childhood recognize, understand, and manage six basic emotions, namely happy, sad, angry, afraid, disgusted, and surprised. Development is carried out using the Research and Development (R&D) model with the stages of needs analysis, design design, product development, implementation, and evaluation. Media is made using PowerPoint, iSpring Suite, and 2Web Apk Builder so it can be accessed as an interactive application. The test results show that EmoPlay is considered appropriate and attractive by psychologists, visual communication design experts, teachers, and children who are users. Feedback from experts encourages the addition of voice over features, mascot animations, and reward systems to increase the attractiveness and effectiveness of the media. Thus, EmoPlay can be an alternative to innovative learning media that is fun and supports the development of emotional regulation in early childhood.